A Rare Cause of Pulmonary Nodules Diagnosed as Angiosarcoma Was Misdiagnosed as Vasculitis and Wegener’s Granuloma in an Elderly Man: A Case Report - Wang, Peixia; Xu, Liqian; Yang, Yunmei (Frontiers in Oncology, 2021)
Background Angiosarcoma is a rare, highly malignant tumor prone to recurrence and metastasis. Angiosarcoma is insidious in the initial stage, and its clinical manifestation lacks specificity. The diagnosis is based on histopathology and immunohistochemistry findings. Case presentation A 73-year-old man was hospitalized following complaints of persistent cough 6 months and hemoptysis for 2 months. Anti-infective treatment was ineffective. A CT-guided percutaneous core needle biopsy of pulmonary lesions revealed organized pneumonia, and the removed skin of purpuric rash area on the left calf revealed vasculitis. Chest CT was used during the patient follow-up. Hormonal therapy combined with immunoglobulins did not lead to improvement, and there was rapid progression of the lung lesions. Subsequently, the patient underwent a surgery, the diseased tissue was separated and removed completely beside the left submandibular gland under local anaesthesia. The immunohistochemical staining indicated CD31 (+) and CD34 (+) confirming a diagnosis of metastatic angiosarcoma. The expression of PD-L1 was 70%, therefore, anlotinib and pembrolizumab treatments were initiated. The patient eventually died. Conclusion Angiosarcoma is a malignant tumor in the clinic that lacks typical and specific signs and symptoms. The diagnosis depends on immunohistochemistry, which requires repeated biopsies of multiple sites in highly suspected cases.